Clinical outcome of muscle invasive carcinoma urinary bladder patients treated with bladder preservation protocol - Joseph, John; Kumar, Aswin; Mathews, Susan; Krishna, Jagathnath K. M.; James, Francis V. (International Journal of Research in Medical Sciences, 2020)
Background: To evaluate the outcome in terms of bladder preservation in muscle invasive urinary bladder patients treated with radical radiotherapy. Methods: A total of sixty patients with muscle invasive bladder cancer who were treated between 2011 and 2013 with bladder preservation protocol were identified. Thirty-two patients were stage T2 disease, rest were T3 and T4. Initial TURBT was reported complete in 24 of the total 60 patients. All patients received 60 to 64Gy to the whole bladder. Results: The follow-up range was 3 to 72 months. One year follow-up proportion was 78%. The median progression free survival was 40months. Early stage (T2) and advanced stage (T3 and T4) had progression free survival of 87.8% and 48.5% respectively at one year follow-up with a p value of 0.001. Thirty-six patients who had an incomplete Transurethral resection of bladder tumor (TURBT) initially had a statistically significant lower PFS compared to those patients who had a complete TURBT with a p value of 0.029. Twenty-nine patients were disease free with an intact bladder during the follow-up period providing a bladder preservation rate of 48%. Conclusions: A bladder-conserving protocol with radiotherapy provides encouraging results with nearly half of the patients able to retain a disease-free bladder. Proper patient selection with early stage disease and those with complete TURBT may further improve the bladder preservation rates.